A cross sectional overview of digital eye strain: a growing health concern in this digital age in central India (Madhya Pradesh) - Sanodiya, Ishan; Kujur, Anubhuti; Sirohi, Suraj; Khatri, A. K. (International Journal Of Community Medicine And Public Health, 2019)
Background: The physical discomfort and collection of symptoms after digital screen use for longer than two hours at a time is referred by the Vision Council as digital eye strain (DES). Common symptoms of DES are eyestrain, headache, blurred vision, dry eyes and pain in neck and shoulders. This study aims to know about the prevalence; factors associated with and awareness about preventive measures for DES among college students. Methods: A cross-sectional study was conducted for 2 months in 2017 among randomly selected 200 college students of 20 to 30 years of age in Indore city of Madhya Pradesh using a pre-designed semi-structured questionnaire. Results: Mean age of participants was 22.5 years; of which 58% were females. Of the respondents, 89.5% (179 students) reported experiencing DES. Average distance from digital screen, brightness level of digital device, use of digital device before going to sleep and awareness about appropriate distance of digital screen from eyes had statistically significant association with having digital eye strain. 98% of respondents were unaware of the term DES while >60% did not have knowledge about the harmful blue light emitted by digital devices, protective use of digital screen filters, appropriate distance of viewing digital screen and the 20-20-20 rule of taking breaks in between screen time. Conclusions: Since digital device use is a necessary evil; better ergonomic practices to avoid DES should be adopted. Opportunistic health promotion and patient education undertaken by ophthalmologists on an OPD basis is one solution.